Pengembangan Ekonomi Lokal Melalui Badan Usaha Milik Desa Berbasis Usaha Mikro, Kecil, Dan Menengah Produk Olahan Hasil Pertanian Di Kecamatan Puncu Kabupaten Kediri - Putri, Nabilla Nuraini Setiawan; Talkah, Abu; Supriyono, Supriyono (Universitas Islam Kadiri, 2024)
Rural development has a very important and strategic role in the framework of national development and regional development, because it contains elements of equitable development and the results can directly affect the interests of the majority of people living in rural areas in relation to welfare improvement activities. However, because UMKMs in Puncu District have local economic potential that has not been optimally handled, an institution is needed that can partner UMKMs as partners to develop the local economy and a suitable institution to become a partner for the community's economic progress is BUMDesa. So that BUMDesa has a very strategic role in driving the community's economy as well as being a pillar of democracy in the countryside, because BUMDesa requires harmonious synergy between the Village Government as the owner of capital and the community as the manager. The type of research used is qualitative research with a descriptive approach and case study method. Using data collection techniques in the form of observation, interviews, documentation, and literature study. The results of the study show that 1. Each BUMDesa has a different role for UMKMs. 2. Not all UMKMs have an R/C ratio of 1.3 and BUMDes have competitiveness from the connection aspect. 3. Both BUMDesa and UMKM have implemented a cluster system from the location and marketing aspects. 4. Institutions are well formed and run well too. 5. Human resources in BUMDesa in each village have not been fulfilled and all matters are still being handled by operational implementers. And not all UMKMs have qualified human resources. 6. Almost all UMKM and BUMDesa in Gadungan Village, Sidomulyo Village, and Puncu Village definitely use modern technology, namely when marketing their products.